Analgesic Efficacy and Safety of Local Infiltration of Tramadol in Pediatric Tonsillectomy Pain: A Systematic Review and Meta‐Analysis. Issue 5 (26th February 2020) - Tsaousi, Georgia G.; Chatzistravou, Anastasia; Papazisis, George; Grosomanidis, Vasilios; Kouvelas, Dimitrios; Pourzitaki, Chryssa
Abstract: Objectives: The aim of this systematic review and meta‐analysis was to appraise clinical evidence of the impact of peritonsillar infiltration of tramadol, on postoperative pain control and the occurrence of adverse effects in children undergoing tonsillectomy. Methods: A database search was conducted to identify randomized controlled trials (RCTs) pertinent to peritonsillar infiltration of tramadol compared to no treatment (placebo) or other analgesic regimens. The outcomes of interest were postoperative pain intensity, time to first analgesic demand, rescue analgesic consumption up to 24 hours after intervention, and the occurrence of adverse events. Results: Twelve RCTs enrolling 972 pediatric patients were selected for qualitative analysis, among which eight were suitable for meta‐analysis. Tramadol infiltration induced a significant reduction of pain intensity up to 24 hours post‐tonsillectomy (mean difference [MD], −2.31; 95% confidence interval [CI], −3.49 to −1.12; P < 0.001; I 2 = 97%) and time to first analgesic (MD 180.54; 95% CI, 56.91 to 304.18; P = 0.004; I 2 = 99%), with no profound impact on postoperative nausea and vomiting (risk ratio [RR] 0.98; 95% CI, 0.73 to 1.32; P = 0.90; I 2 = 0%) compared to the placebo group. The analgesic efficacy of tramadol infiltration was equivalent to the local or systematic use of ketamine or infiltration with local anesthetics. This effect was further enhanced when tramadol infiltration served as an adjunct to other analgesic interventions. No serious adverse events were reported. Conclusions: In children undergoing tonsillectomy, peritonsillar infiltration of tramadol is associated with a postoperative analgesic benefit when compared to placebo, with negligible adverse events. Yet, no definite conclusion can be drawn due to the low quality, considerable heterogeneity, and paucity of the available data.